Cooperative learning that features a culturally appropriate pedagogy - Nguyen, Phuong-Mai; Terlouw, Cees; Elliott, Julian; Pilot, Albert; Elliott, Julian (British educational research journal, 2009)
Many recent intercultural studies have shown that people cooperate with each other differently across cultures. We argue that cooperative learning (CL), an educational method originating in the USA and with fundamental psychological assumptions based on Western values, should be adjusted to be culturally appropriate for any non‐Western cultures in which it is applied. In the light of this assertion, this paper reports a series of experiments conducted in Vietnamese upper‐secondary schools. One group was provided with a series of lessons designed according to mainstream CL practice. Another group was provided with similar lessons but these were modified so as to be more culturally appropriate in terms of leadership, reward allocation and group composition. Findings show that (1) the role and the type of leadership, although not a key element of mainstream CL theories and practice, proved to be influential; (2) groupings based upon existing friendships, rather than upon cognitive ability, appeared to be important. A key finding was that the group receiving a culturally modified programme appeared to work harder during, and gain more satisfaction from, collaborative learning activities.